Pendampingan Pembelajaran Siswa di SD Negeri 1 Prajegan Melalui Team Teaching Dalam Upaya Untuk Meningkatkan Mutu Pendidikan - Mukarromah, Annisa; Asfahani, Asfahani; Fauziyati, Wiwin Rif'atul (Social Science Academic, 2024)
Supporting student learning in elementary schools involves various efforts to help students understand subject matter, overcome learning difficulties, and develop optimally. The objectives of service in elementary schools usually include various aspects that support the development of students, teachers, and the school community as a whole to improve the quality of education . Improving the quality of learning and developing student skills, improving the school environment, and supporting student welfare. Service methods in elementary schools can vary depending on the specific goals and context of the service program, including helping students with learning difficulties through additional sessions or individual tutoring. The results of service in elementary schools depend on the objectives and type of service program implemented, such as improving students' academic achievement and understanding of subject matter through additional guidance and support, improving teachers' skills and knowledge in teaching and classroom management, a better learning environment and supporting learning development student.